Selected Topics on Computed Tomography - Wang, Dongqing (IntechOpen, 2013)
This book is a research publication that covers developments within the Diagnostics field of study. The book is a collection of reviewed scholarly contributions written by different authors and edited by an expert with specific expertise. Each scholarly contribution represents a chapter which is complete in itself but related to the major topics and objectives. The target audience comprises scholars and specialists in the field.